Investigating the Impact of Financial Compensation, Transformative Leadership Style, and Work Motivation on Job Satisfaction and Performance among Staff Members of the Indonesian House of Representatives (DPR RI) - Andi Anugerah Wijaya; Hasanudin Hasanudin (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to determine and analyze the influence of financial compensation, transformational leadership style, work motivation on the performance of staff members of the DPR RR Nasdem Party faction through job satisfaction. Determination of the population sample was calculated using the Hair formula with a total of 110 samples. Data collection uses questionnaires and interviews and data processing uses Structural Equation Model (SEM). The research results found that financial compensation and work motivation had a significant influence on employee satisfaction and performance. Apart from that, job satisfaction also has a significant influence on employee performance. Meanwhile, the job satisfaction variable is only able to mediate work motivation and financial compensation, while the transformational leadership style cannot be mediated by the job satisfaction variable. For the Nasdem party faction, they can increase the financial compensation given to the staff of DPR members from the Nasdem party faction so that they can increase employee job satisfaction.